Providing Sexual Companionship for Resources: Development, Validation, and Personality Correlates of the Acceptance of Sugar Relationships in Young Women and Men Scale (ASR-YWMS) - Birkás, Béla; Meskó, Norbert; Zsidó, András N.; Ipolyi, Dóra; Láng, András (Frontiers in Psychology, 2020)
A sugar relationship is a transactional sexual relationship in which a younger partner (sugar baby/boy) offers companionship and sexual services to a much older partner (sugar daddy/mommy) in return for material compensation. One aim of the present study was to develop an attitude scale assessing young women’s and men’s acceptance of sugar relationships. Another aim was to explore the possible associations of the acceptance of sugar relationships with psychological functioning in an intimate partner relationship and in a sexual relationship and with certain socially undesirable personality traits. Two online studies were conducted with a total number of 2052 participants (1879 women; age = 18 to 28 years). The results show that the Acceptance of Sugar Relationships in Young Women and Men Scale (ASR-YWMS) is a reliable and valid measure of young people’s attitude towards sugar relationships. The studies revealed that young women’s and men’s accepting attitude towards sugar relationships was positively associated with unrestricted sociosexuality, a game-playing love style (Ludus), self-focused sexual motivation (Study 1; N = 319; 272 women and 47 men), and with socially undesirable traits such as Machiavellianism, subclinical psychopathy, and a borderline personality organization (Study 2; N = 1733; 1607 women and 126 men). These findings suggest that a relatively high level of acceptance of sugar relationships is part of a mating strategy focused on opportunities of maximizing resources. This utilitarian, risk-taking and exploitative attitude is characteristic to a fast life history strategy, and it is a fundamental organizing principle of psychological and sexual functioning in intimate partner relationships.